PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM DAN SOAL DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 13 PADANG - Elfiyanti, Melda; Putra, Atus Amadi; Anggraini, Villia (STKIP PGRI Sumbar, 2013)
This research was made because of the lack of studentsâ experience in discussing so that they find difficulty in sharing opinion and ideas with their friends. It makes the students lack of mathematics comprehension concept that is seen in the VIII of students SMPN 13 Padang on 2012/2013. This research is aimed to determine studentsâ mathematics comprehension that applies cooperative of learning Technigue Berkirim Salam Model dan Soal that is followed by quiz is better than the comprehension of studentsâ mathematic concept that applies conventional learning in the VIII grade of SMPN 13 Padang. This research is an experimental research which is designed randomized to the subjects. The population of this research is SMPN 13 Padang students at the VIIIÂ grade on 2012/2013 learning period that consists of seven classes. The sample was taken by randomly, Where VIII5 as the experimental class and VIII6 as the controlling class. The instruments that are used in this research are quiz and the comÂprehension of mathematics concept test. The test that is used is a kind of an essay with reliabiliÂties is 0,88. The data analysis technique is t crucible with one section. Based on the analysis data, it is known that the two samples distribute normally and homogeneous in Î± = 0,05. The result of this hypothesis is Â Â Â Â P-value = 0,000 was less than Â so that this hypothesis can be accepted. It can be concluded that stuÂdentsâ mathematÂics comprehension that applies cooperative of learning Technigue Berkirim Salam dan Soal that is followed by quiz is better than conventional applying learning in the VIII grade of SMPN 13 Padang.